In vitro derivation of megakaryocytes and platelets from induced pluripotent stem cells: developmental foundations and translational perspectives - Mazurek, Maciej; Młynarski, Wojciech; Grzela, Dawid P. (Frontiers in Immunology, 2025)
For centuries, hematologists have strived to develop increasingly sophisticated systems and therapeutic protocols for replenishing the blood. However, demographic shifts have led to a growing demand for blood-derived products, and the number of eligible donors continues to decline, raising concerns regarding the future availability and cost-effectiveness of transfusion therapies. Advances in our understanding of molecular hematopoiesis, coupled with the development of precise gene-editing tools such as CRISPR/Cas9 and the advent of induced pluripotent stem cell (iPSCs) technology, have opened new avenues for the generation of functional blood components in vitro. The ability to reprogram somatic cells into pluripotent states offers a virtually unlimited and ethically acceptable source of patient-specific or universal donor-compatible cells for both research and therapeutic applications. This review summarizes the current strategies for the in vitro generation of megakaryocytes and functional platelets from iPSCs and outlines the developmental foundations of primitive and definitive hematopoiesis that underpin these efforts. Furthermore, we emphasize strategies aimed at improving maturation and yield, along with emerging approaches in HLA editing and immune tolerance designed to overcome alloimmune barriers in transfusion medicine.